Patient confidence and quality of life in idiopathic pulmonary fibrosis and sarcoidosis - Kotecha, Jalpa; Atkins, Christopher; Wilson, Andrew (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Idiopathic pulmonary fibrosis (IPF) and sarcoidosis impact significantly on health-related quality of life (HRQOL). There are few studies on the impact of patient confidence on HRQOL in these conditions. Objectives: 1. To investigate whether patient confidence is associated with HRQOL, anxiety, depression, dyspnoea or fatigue. 2. To assess if patient confidence is associated with inpatient admissions, access to community healthcare and, for IPF patients, mortality and disease severity. Methods: Study participants self-completed seven questionnaires: Hospital Anxiety and Depression Scale, EuroQol 5D (EQ5D), King’s Brief Interstitial Lung Disease questionnaire, St George’s Respiratory Questionnaire, MRC dyspnoea scale, Fatigue Assessment Scale and a non-validated questionnaire assessing patient confidence, symptom duration and access to community healthcare. Lung function and follow-up data were collected from hospital electronic databases. Spearman’s rank correlation coefficients were calculated to assess for correlation between patient confidence, questionnaire variables and inpatient admissions. Chi-square tests were performed to assess for association between patient confidence, mortality and disease severity. Results: 75 IPF patients and 69 sarcoidosis patients were recruited to the study. Patient confidence in IPF was significantly negatively correlated with depression and fatigue, and significantly positively correlated with EQ5D scores, but not healthcare outcomes. No associations were found between confidence and any of the variables assessed in sarcoidosis. Conclusions: Lower levels of confidence in IPF patients are associated with higher levels of depression and fatigue and worse HRQOL. Efforts should be made to improve patient confidence to assess the impact on HRQOL.